STUDI LITERASI MAHASISWA FAKULTAS MIPA UNIVERSITAS UDAYANA TERHADAP APLIKASI INVESTASI SEBAGAI INOVASI FINANCIAL TECHNOLOGY (FINTECH) - ADI, I KADEK YUDHA PRAMANA; SUKARSA, I KOMANG GDE; KENCANA, EKA N. (E-Jurnal Matematika, 2025)
Technological advancements have brought significant transformations to various aspects of life, including the financial sector. The emergence of financial technology (fintech) is clear evidence of innovation that shifts traditional methods of managing finances into more modern solutions, offering practical and affordable options. One popular form of fintech is investment applications, which make it easier for the public, especially younger generations like students, to engage in investment activities. This study aims to analyze the factors influencing user decisions in using investment applications among students, focusing on perceived benefits and user experience. The study was carried out at the Faculty of Mathematics and Natural Sciences, Udayana University, employing factor analysis. The research involved a sample of 132 respondents, with purposive sampling as the chosen sampling technique. The results show that the factors influencing user decisions in using investment applications are application benefits and user satisfaction, as well as user experience and investment routines. These two factors can explain 91.466% of the diversity in the use of investment applications, with the dominant factor being application benefits and user satisfaction.